2009
DOI: 10.1016/j.mcn.2009.05.007
|View full text |Cite
|
Sign up to set email alerts
|

FGF14 N-terminal splice variants differentially modulate Nav1.2 and Nav1.6-encoded sodium channels

Abstract: The Intracellular Fibroblast Growth Factor (iFGF) subfamily includes four members of the structurally related FGF superfamily. Previous studies showed that the iFGFs interact directly with the pore-forming (α) subunits of voltage-gated sodium (Nav) channels and regulate the functional properties of sodium channel currents. Sequence heterogeneity among the iFGFs is thought to confer specificity to this regulation. Here, we demonstrate that the two N-terminal alternatively spliced FGF14 variants, FGF14-1a and F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
175
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(188 citation statements)
references
References 45 publications
(125 reference statements)
12
175
1
Order By: Relevance
“…In addition to its role in channel inactivation, the C‐terminal domain of Na v 1.6 interacts with several proteins that regulate channel trafficking or activity 20, 23, 30. To determine whether mutations at Arg1872 disrupt these interactions, we tested the effect of the p.Arg1872Trp mutation with substitution of the large uncharged tryptophan residue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its role in channel inactivation, the C‐terminal domain of Na v 1.6 interacts with several proteins that regulate channel trafficking or activity 20, 23, 30. To determine whether mutations at Arg1872 disrupt these interactions, we tested the effect of the p.Arg1872Trp mutation with substitution of the large uncharged tryptophan residue.…”
Section: Resultsmentioning
confidence: 99%
“…The pHA‐Na v 1.6‐CT cDNA construct containing the 213 amino acid C‐terminal domain of Na v 1.6 with an N‐terminal HA epitope tag20 was kindly provided by Dr. David Ornitz, Washington University. The substitution p.Arg1872Trp was introduced as above and the open reading frame was completely sequenced.…”
Section: Methodsmentioning
confidence: 99%
“…Among the intracellular VGSC regulators are the FGF homologous factors (FHFs), noncanonical members of the FGF superfamily that are neither secreted nor appear to function as growth factors (15)(16)(17)(18). Rather, the four FHFs (FGF11-FGF14) each contain a VGSC interaction site within a homologous FGF-like core domain (19,20) and exert variable effects on VGSC functional properties (21)(22)(23). The importance of FHFs is underscored by loss-of-function or dominant negative mutations in specific FHFs associated with various neurological disorders, which have been attributed, at least in part, to VGSC dysfunction.…”
mentioning
confidence: 99%
“…Among this group of molecules, FGF14 stands out for its potent, specific, and diverse modulatory actions on Nav channels in the CNS, features that have been attributed to its unique nonconserved N-terminal domain (4 -7, 14). A number of in vitro experiments and studies in heterologous cells have examined the relative binding affinities of FGF14 to various Nav isoforms and evaluated the functional effects of FGF14 expression on Na ϩ currents, especially the ones encoded by the neuronal Nav1.2 and Nav1.6 isoforms (6). It has been shown that through high affinity binding to the intracellular C terminus of the ␣ subunit of Nav channels (7), FGF14 potently modulates amplitude and voltage dependence of Na ϩ currents, producing functional outcomes on Na ϩ currents of magnitude and direction that depend upon the channel isoform and the cell background (4 -6).…”
mentioning
confidence: 99%